Анализа корелације серумског ЛАП-а, ГДГФ-а и феритина у прогнози акутне мијелоидне леукемије: Серумски ЛАП, ГДГФ и феритин у прогнози АМЛ-а - Ma, Naixia; Zhou, Rui; Ge, Yaqi; Huan, Yahong (Journal of Medical Biochemistry, 2026)
Objective To look into the correlation analysis between blood levels of Latency associated peptide (LAP), Glioma-derived growth factor (GDGF), Ferritin, Neutrophil/Lymphocyte ratio, and Albumin/Fibrinogen ratio and the prognosis of patients with acute myeloid leukemia (AML).Methods The study group consisted of 384 AML patients who were hospitalized to the hospital between May 2022 and October 2024, whereas the control group was made up of 192 healthy people who were examined physically while they were there. The levels of serum LAP, GDGF, and Ferritin and the Neutrophil/Lymphocyte ratio and Albumin/Fibrinogen ratio were compared. Following their discharge, the study group's participants were monitored for a total of 12 months. Patients having a favorable prognosis and those with a bad prognosis were divided into two groups. The factors predicting a poor prognosis in AML patients were examined using multivariate logistic regression and a comparison of the clinical data from the two groups. Receiver operating characteristic (ROC) curves were developed to evaluate the predictive significance of LAP, GDGF, Neutrophil/Lymphocyte ratio, Albumin/Fibrinogen ratio, and Ferritin for a poor prognosis in AML patients.Results The GDGF level, Ferritin, Neutrophil/Lymphocyte ratio, and Albumin/ Fibrinogen ratio were all higher than those in the control group (P